1999
DOI: 10.1002/(sici)1097-0193(1999)7:3<166::aid-hbm3>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of brain activation patterns using a 3-D scale-space primal sketch

Abstract: A fundamental problem in brain imaging concerns how to define functional areas consisting of neurons that are activated together as populations. We propose that this issue can be ideally addressed by a computer vision tool referred to as the scale-space primal sketch. This concept has the attractive properties that it allows for automatic and simultaneous extraction of the spatial extent and the significance of regions with locally high activity. In addition, a hierarchical nested tree structure of activated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…One might consider integrating the TFCE score not just over the cluster-forming height/extent in the way proposed, but also integrating over a second-dimension -data smoothing extent. Although we have tried to find an optimal data smoothing extent, for the reasons discussed above, there may still be value in searching/integrating over a range of smoothings, as suggested in scale-space and wavelet literature going back more than a decade [Worsley et al, 1996a, Lindeberg et al, 1999, Coulon et al, 2000, Fadili and Bullmore, 2004, Flandin and Penny, 2007, Van De Ville et al, 2007. Further investigations in these directions will be the subject of future work.…”
Section: Discussionmentioning
confidence: 99%
“…One might consider integrating the TFCE score not just over the cluster-forming height/extent in the way proposed, but also integrating over a second-dimension -data smoothing extent. Although we have tried to find an optimal data smoothing extent, for the reasons discussed above, there may still be value in searching/integrating over a range of smoothings, as suggested in scale-space and wavelet literature going back more than a decade [Worsley et al, 1996a, Lindeberg et al, 1999, Coulon et al, 2000, Fadili and Bullmore, 2004, Flandin and Penny, 2007, Van De Ville et al, 2007. Further investigations in these directions will be the subject of future work.…”
Section: Discussionmentioning
confidence: 99%
“…Medical applications of the scale-space primal sketch have been developed for analyzing functional brain activation images (Lindeberg et al [117], Coulon et al [29], Rosbacke et al [136], Mangin et al [120]) and for capturing the folding patterns of the cortical surface (Cachia et al [25]). More algorithmically based work on building graphs of blob and ridge features at different scales was presented by Crowley and his co-workers [31,32] using difference of low-pass features defined from a pyramid; hence with very close similarities to differencesof-Gaussians operators and thus the Laplacian.…”
Section: Related Workmentioning
confidence: 99%
“…47 The typical choice is a low-pass Gaussian filter in the spatial domain, which smooths high frequency variation in the data. Several researchers have suggested that the use of Gaussian filters for denoising in the spatial domain introduces unwanted biases, [48][49][50][51][52][53] and that the optimal filter width is a function of the size of activation foci, 50,54 which cannot generally be determined a priori except possibly by reference to underlying neuroanatomy. The low-pass filter approach will also blur and displace activated areas and remove the areas of least activation, reducing spatial resolution.…”
Section: Functional Imaging Of the Brainmentioning
confidence: 99%